THE EFFECT OF PH AND CALCINATION TEMPERATURE ON THE ZrO2 PHASE FORMATION FROM NATURAL ZIRCON SAND OF KERENG PANGI - Abdullah, Mohammad; Triwikantoro, Triwikantoro; Umamah, Chairatul; Andi, Herman Jufri (Jurnal Neutrino, 2021)
In this research ZrO2 has been synthesized from Kereng Pangi zircon sand in Central Kalimantan through alkali fusion-coprecipitation method. Firstly, zircon sand (ZrSiO4) was purified to reduce impurities by magnetic separation, cleaned using an ultrasonic cleaner, soaked/leached with HCl 2 M for 12 hours and leached with HCl at 60 ºC for 3 hours. Secondly, alkali fusion was done with KOH as an alkali. This product was then washed by water and dried before leached with HCl 30% at 90 ºC for 30 minutes to precipitate and seperate Silica from Zircon. ZrO2 filtrate (ZrOCl2) precipitated with NH4OH at pH 4, pH 7, and pH 10 forms Zr(OH)4 gel. Zr(OH)4 gel was dried and characterized by DTA-TGA, which was then followed by calcination based on DTA TGA results at temperature ranges of 550 ºC - 700 ºC to produce ZrO2. XRD results show that single tetragonal phase of ZrO2 is formed in all variations of pH precipitation and calcination temperature. An analysis using MAUD software show that crystal size reduces as the increase in precipitation of pH. The crystal size results are 110 nm, 66 nm and 48 nm at pH 4, pH 7 dan pH 10 at 700 ºC, respectively. Moreover, XRF results show that ZrO2 with purity is at around 95.8 % at pH 4 and 96.3 % at pH 7 and pH 10.